Analysis of Regional Competitiveness Index of Banten Province on Human Resources Aspects: Analisis Indeks Daya Saing Daerah Provinsi Banten pada Aspek Sumber Daya Manusia - Surya, Shabrina Naras; Nurita, Nurita; Siregar, Johannes Hamonangan; Berliana, Nani Grace (Universitas Muhammadiyah Sidoarjo, 2023)
An important factor influencing the success of regional development, one of which is the human resources (HR) that have a role in increasing the productivity and competitiveness of a region. An analysis of the competitiveness of a region needs to be carried out to identify weaknesses and strengths in human resource aspects that will have an impact on economic performance and people's welfare. This study aims to analyze the Regional Competitiveness Index (IDSD) of Banten Province in terms of human resources using several indicators, including education level, availability of employment, health, and investment environment. The method used is descriptive analysis and regional competitiveness index calculation. The data used in this study were obtained from the National Research and Innovation Agency. The results of the study show that Banten Province has an IDSD value on the health pillar of 3.75. From the health pillar, there are 3 regencies/cities that have a higher IDSD score, namely Tangerang Regency with a score of 3.85, Tangerang City with a score of 4, and South Tangerang City with a score of 4. Meanwhile, the IDSD score on the skills pillar has a score of 3.44. There were only 3 that had a higher IDSD score, namely Tangerang City with a value of 3.86, Cilegon with a value of 3.53, and South Tangerang City with a value of 3.79. Therefore, it is necessary to make efforts to improve the quality of human resources in Banten Province by taking into account the factors that affect competitiveness, including education, availability of fields, employment, health, and the investment environment.